Desejos de liberdade: tutelas, fugas e a fundação da colônia orfanológica de Pindamonhangaba/SP (1888-1892) (Ágora Journal, 2020)
Abstract: The object of study of this research is the comprehension of the work’s sphere in Pindamonhangaba society, located in Paraíba Valley, by the analysis of the exploitation of the work of under aged, of the ingenuos and unprotected orphan, children of former slaves, released and poor single women was widely spreaded between many farmers and elite members in the slavery end. When being tutores, such minors were directed to the work in farming, from the consult of the tutelage’s documents processed in the judgment of orphans, from 1888 to 1892. Once more the black family was separated, this time by tutelage, so we stand out the escapes of children under guardianship.
Keywords: keywords: tutelage, orphans, post-abolition of slavery.